Động học hấp phụ asen trong nước bởi cột phản ứng chứa hạt hydroxit lớp đôi - Nhật Hà, Hồ Nguyễn; Mai Thơ, Nguyễn Thị; Phương Diệu, Nguyễn Thị; Kim Phượng, Nguyễn Thị (Vietnam Journal of Chemistry, 2016)
The LDHs-polymer beads (MgAl-polymer beads or MgFe-polymer beads) were generated by impregnating synthetic LDHs (MgAl or MgFe) into polymer (alginate/polyvinyl alcohol-glutaraldehyde gel bead). A Scanning Electron Microscope (SEM) and an X-Ray Diffractometer (XRD) were used to analyze the properties of LDHs-polymer beads. SEM images showed that the surface of LDHs-polymer beads was heterogenerous demonstrating that of the LDHs powders were intermingled with polymer. The adsorption of arsenic onto the LDHs-polymer beads was investigated by performing column experiment. Maximum removal capacity (50-60 %) was found at 0.24 L.h-1 flow rate, 25 cm LDHs-polymer beads height and 300-500 µg.L-1 influent As concentration. The experimental data were well fitted with the Thomas model. This study approved that LDHs-polymer beads have high potential for arsenic removal as adsorptive media. Keywords. LDHs-polymer beads, column experiment, arsenic.